2020
DOI: 10.3390/nu12051325
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Intake during Pregnancy and Post-Partum: ECLIPSES Study

Abstract: Pregnancy and post-partum are critical periods in which nutritional intake is essential to maternal and child health. Our aim was to describe dietary intake during pregnancy and post-partum and assess its adequacy. A longitudinal study was conducted on 793 pregnant women. Data about maternal characteristics, health, diet and lifestyle were assessed. Energy and nutritional intake were compared to the Recommended Dietary Allowances (RDA). The results showed that the intake of energy (82.6%), protein (80.6%) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 38 publications
1
25
1
2
Order By: Relevance
“…Our results are consistent with their findings, as they also found an increase in SFA and MUFA during pregnancy. This increase could be due to an increase in biosynthesis to cover requirements, since the rise in serum concentration may not be related to the small variation in the mothers’ dietary intake [ 30 , 31 ], as our research group found in this sample of healthy pregnant women in relation to their intake during pregnancy [ 32 ]. The SFA may play a key role in supporting foetal membrane growth, as the SFA bio-magnification process could help to satisfy AA demands in foetal circulation and DHA in the brain [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with their findings, as they also found an increase in SFA and MUFA during pregnancy. This increase could be due to an increase in biosynthesis to cover requirements, since the rise in serum concentration may not be related to the small variation in the mothers’ dietary intake [ 30 , 31 ], as our research group found in this sample of healthy pregnant women in relation to their intake during pregnancy [ 32 ]. The SFA may play a key role in supporting foetal membrane growth, as the SFA bio-magnification process could help to satisfy AA demands in foetal circulation and DHA in the brain [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study was approached from a pregnancy perspective. The fact that dietary intake was assessed only during the 2nd trimester, may be considered to be a limitation, since, the portrait of dietary intake may not be typical for the entire pregnancy period; nevertheless, previous studies have suggested that there is stability in dietary intakes across trimesters [57,68]. As stated in the Introduction Section, according to FIGO there is a cycle of passing "health capital" from one generation to the next [5].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…During the period of pregnancy, pregnant women need an extra intake of calories of 300-400 kcal per day [32], [33]. They should consume balanced daily nutrition to prevent them from the excess energy that leads to the risk of obesity during pregnancy [14], [15], [34]. The results of this study indicated that the consumption of daily nutrition containing carbohydrates is associated with the incidence of pre-eclampsia with the p = 0.00 (OR = 3.545, 95% CI = 2.098, 13.158).…”
Section: Analysis Of Nutritional Adequacy and Incidence Of Pre-eclampsiamentioning
confidence: 99%
“…Another impact of pre-eclampsia is growthrelated disorders, the development of intrauterine growth retardation [8], [10], [11], and intrauterine fetal death [12], [13]. Pre-eclampsia may occur during the antenatal, intrapartum, and postnatal with symptoms of hypertension, protein in the urine (proteinuria), and edema [6], [14], [15]. Although the cause of pre-eclampsia is still unclear, there seem to be some specific factors such as age, nulliparity, body mass index, mother's diet, hypertension, preexisting, history of pre-eclampsia, kidney disease, and diabetes mellitus [4], [16], [17], [18], [19].…”
Section: Introductionmentioning
confidence: 99%